Objetos de aprendizaje como herramientas digitales didácticas para la enseñanza virtual en la asignatura de matemáticas aplicados en los estudiantes de tercer año de educación básica de la escuela de educación básica "Manuelita Sáenz", parroquia Gabriel Ignacio de Veintimilla, provincia Bolívar, cantón Guaranda en el periodo académico 2021 – 2022 - Chiriguayo Ramírez, Ana Flor (2022)
Identifying the causes and effects of the issue raised in the technological proposal is essential, since it allows measuring the benefit it may have in different areas and determining the significance of using it in the same way in the subject of mathematics, therefore, through the dependent and independent variables, the relevance it will have within the virtual education of macro, meso, micro, and bidirectional character was analyzed, it promotes and covers the gap that provides not having adequate resources to learn, so this affects the students of the aforementioned educational institution. Since the last decade, the creation of learning objects based on the use of ludic resources has attracted much attention, with the purpose of improving the teaching-learning process of the students, where the technological proposal was developed, focused on the students of the third year of Basic Education of the School of Basic Education "Manuelita Saenz", Parish Gabriel Ignacio de Veintimilla, Province Bolivar, Canton Guaranda. Translated with www.DeepL.com/Translator (free version) the degree of importance of the work is based on the fact that learning objects should be created and used virtually to promote meaningful learning, which, through the insertion of didactic content, allows students to awaken their interest and motivation to learn regardless of the limitations they have at home or in the classroom. The first starting point was to interview the teacher of the educational institution and to analyze the type of methodology she used to teach the activities; being a community educational center that had to adapt to virtual education, it is imperative to carry out a constant redefinition of its resources that covers the possibilities to reach its students or users in general, so that they can take advantage of the most modern advances found in TIC. Carrying out the insertion of different types of didactic digital materials with various resources such as audio, images and videos takes a dynamic and striking learning environment; within this stage it is determined the identification of basic requirements to develop the technological proposal that covers the creation of learning objects according to the contents that are being addressed with students and the Ardora 9 application was chosen. Ardora 9, provides the benefits and advantages that a teacher needs to make use of when integrating digital didactic content during the creation of playful materials and is an application that the author can use freely, through SCORM packaging, that is, it can be saved as an extension type .HTML, its advantage is that it can be run for free without internet. The learning objects have helped different users and explicitly the students with low knowledge today more than ever in a virtual education raised by the COVID-19.